Spatio-temporal error concealment scheme based on H.264/AVC - FENG Bin; ZHU Guang-xi; LIU Wen-yu (Tongxin xuebao, 2007)
In order to reduce the influence of transmission errors on the reconstructed image quality in decoder,a novel spatio-temporal error concealment scheme was proposed.A hypothesis was made that the corrupted macro blocks（MB） distributed randomly in the frame which is sufficiently realistic and extensively used in literature.Firstly a directional in-terpolation based spatial error concealment algorithm was used which introduces a method similar with the intra predic-tion in the encoder.Then an 8×8 block based enhanced temporal error concealment algorithm was proposed,which im-proved the ability to deal with the high motions areas.Finally,a switch strategy between spatial and temporal error conceal-ment algorithm was addresse.It chooses an appropriate algorithm based on the adjacent MB coding modes.Experimental results demonstrate that the proposed scheme is prior to the algorithms in H.264/AVC both in objective and subjective quality.